Marc Bloch, sociology and geography : encountering changing disciplines - Friedman, Susan W. (Cambridge studies in historical geography, 1996)
The French historian, Marc Bloch (1886-1944), has been very influential in the development of both history and social science. Comparative historians, historical geographers, and historical sociologists have all pointed to his work as a model. This book is the first detailed examination of the relationship of the work of Bloch to both Durkheimian sociology and Vidalian geography. Through a careful examination of the debates in which he was involved and the institutional circumstances in which he worked, it places Bloch's work within its intellectual context, and assesses the nature of his contribution. Professor Friedman argues that, despite the frequent claims of scholars in history, sociology and geography, Bloch did not adopt either the Durkheimian or Vidalian approach. Both disciplines were central to his intellectual development and his relationships to them were interdependent. The result was his own highly acclaimed approach.